MAIN READING TYPES AND APPROACHES TO TRADITIONAL TEXT ANALYSIS USED IN GERMAN LANGUAGE CLASSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The following article discusses the main types of reading used in German language classes and approaches to traditional text analysis, and lists the different types of reading comprehension.